If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(r + -5 + -4p) = 0 Reorder the terms: -1(-5 + -4p + r) = 0 (-5 * -1 + -4p * -1 + r * -1) = 0 (5 + 4p + -1r) = 0 Solving 5 + 4p + -1r = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + 4p + -5 + -1r = 0 + -5 Reorder the terms: 5 + -5 + 4p + -1r = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 4p + -1r = 0 + -5 4p + -1r = 0 + -5 Combine like terms: 0 + -5 = -5 4p + -1r = -5 Add 'r' to each side of the equation. 4p + -1r + r = -5 + r Combine like terms: -1r + r = 0 4p + 0 = -5 + r 4p = -5 + r Divide each side by '4'. p = -1.25 + 0.25r Simplifying p = -1.25 + 0.25r
| 8r+2r-5r--19r+4r=16 | | x + 3y = 10 | | 0.75a=14.25 | | -(0.6)(-0.3x)(1.5)(-1)=b | | (7x^3-15x^2-9)-(3x^3+5x+15)= | | 8b^5+20b^3+2b^2+12b=0 | | 2(x-5)=3-2(7-x) | | 20=s-25 | | 7x+1=2-x | | 2m-m+4m=15 | | 350=140r | | (6x^2+19x+2)+(-4x^2+10x-11)= | | -7+13b+(-6b)-b= | | y-2=7/3(x-6) | | 30+41= | | -5(1-5x)+5(-8x-2)=-4+-8x | | F(x)=5x^2+11x-12 | | -14k--19k-8k=-18 | | 4x^2-14x=2(2x^2-7x) | | 12x+5=17x-10 | | (x^2-4x+4)(x^2+9)= | | y-x^2= | | 4.5x-2=2.5x+8 | | s/19=150 | | 8b^5+20b^3+48H^4x^2=0 | | 14xd=154 | | 14k-19k-8k=18 | | 2(x-5)=4-7(7-x) | | -10-14b-3-(-5b)= | | 4a^2b^7+2ab^4-6ab^7= | | 8y-6x+7x= | | 7x-2(-10+5x)=11 |